Effect of magnetic field on radial dopant segregation in crystal growth by traveling heater method - Sadrhosseini, H.; Sezai, I. (Elsevier France-Editions Scientifiques Medicales Elsevier, 2010)
A three dimensional time dependent computational model is developed to simulate the melt flow, heat transfer and the dopant transport during the growth of Si(1-x)Ge(x) semiconductor crystals by traveling heater method. The effect of static magnetic fields of different orientations on the radial and axial segregation of dopant is analyzed. It is observed that the flow oscillations are damped and flow becomes steady for both horizontal and vertical applied magnetic fields as the Hartmann number increases. It is found that there is an optimum value of Hartmann number beyond which little improvement in uniformity of concentration can be obtained at the growth interface. (C) 2010 Elsevier Masson SAS. All rights reserved.
Keywords: Traveling heater method; Si(1-x)Ge(x); Magnetic field; Segregation; Crystal growth